OPTICAL ABSORPTION IN Ce0 -V 0 EVAPORATE THIN FILMS (Journal of Sciences, Islamic Republic of Iran)
In this work, the optical absorption near the fundamental absorption edge of co-evaporated Ce0 -V20 films is studied. It is found that the fundamental optical absorption in these materials is sharp more like that expected for crystals. It is also found that as the V O content increases, the edge becomes less sharp and shifts towards higher wavelengths